Towards a partnership model for developing core abilities - Cowan, John; Harte, Clarissa (International Journal for Students as Partners, 2023)
A tutor and a student together propose a model for integrated student and staff engagement that concentrates on developing students’ core abilities. They build upon their respective experiences of self-managed problem-based learning and of the purposeful promotion of core abilities. They explore the potential of collaborative interaction between trainee tutors and their students, who are both freshly engaged in self-managed experiential learning. The authors’ use of the Kolb Cycle as a framework is exemplified in the student-author’s experiential learning. They relate and comment upon the tutor-author’s iterative attempts to overlap experiential learning cycles for trainee tutors and their students, and extend the emerging model by adding purposeful peer interactions and regular evidence-based evaluations. Their completed scheme features a partnership wherein tutors’ growing experiences of structuring and facilitating socio-constructivist learning are integrated with students’ reflective reviews of recent developmental experiences.